Análise e projeto do sistema de controle de um módulo de potência com conversores em cascata aplicado a transformadores de estado sólido - Queiroz, Samuel Soares (2016)
This master thesis present the analysis of a power module with cascaded converters applied to solid state transformers. The power module is built by an AC-DC input stage, constituted by full-bridge topology, an DC-DC intermediate isolated stage, formed by the dual active bridge converter (DAB), and an DC-AC output stage composed of full-bridge topology. The central study developed is based on the investigation of the dynamic interactions impedances in the connection points of the converters and power module stability. The criterion of Middlebrook is applied as the basis for determining the margin of interaction of the coupling between rectifier/DAB and DAB/inverter and definition of critical parameters of power and control for the characteristics of the impedance of each stage. The criterion of Nyquist is applied to study the stability margin of the couplings. Due to the inverter operation, there is a significant second harmonic current that generating voltage ripple at 120 Hz in the DC bus that interconnects the power converters. In this sense, this master thesis contributes presenting a theoretical analysis of the effects of voltage ripples in the operation and performance of the power circuit and control system of the DAB converter. The methods of PI control and PI-notch in DAB control system are explored, highlighting that the inclusion of notch filter performs better by enabling the mitigation of the negative effects introduced by the voltage ripple at 120 Hz. Moreover, a methodology study and PI of the project is proposal to achieve better results with this method of control, from the point of view of stability and performance. Experimental and simulation results of the system are included to demonstrate the developed analysis.